Proceedings of the 14th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2008
DOI: 10.1145/1401890.1401948
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic evolution of social networks

Abstract: We present a detailed study of network evolution by analyzing four large online social networks with full temporal information about node and edge arrivals. For the first time at such a large scale, we study individual node arrival and edge creation processes that collectively lead to macroscopic properties of networks. Using a methodology based on the maximum-likelihood principle, we investigate a wide variety of network formation strategies, and show that edge locality plays a critical role in evolution of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
523
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(540 citation statements)
references
References 26 publications
(17 reference statements)
14
523
2
1
Order By: Relevance
“…The first type of approaches is the well-known two- 40 steps strategy, which identifies community structure in each snapshot network by using methods for static networks, and then analyzes the community evolution according to some principles, such as the Jaccard index [13]. The second type of approaches is the generative model [14] which is based on the combination of stochastic block model (SBM) and the state space model or liner dynamic system, i.e., the whole temporal network is represented as a sample of a dynamic generative model.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…The first type of approaches is the well-known two- 40 steps strategy, which identifies community structure in each snapshot network by using methods for static networks, and then analyzes the community evolution according to some principles, such as the Jaccard index [13]. The second type of approaches is the generative model [14] which is based on the combination of stochastic block model (SBM) and the state space model or liner dynamic system, i.e., the whole temporal network is represented as a sample of a dynamic generative model.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…users tend to create and receive links in proportion to their outdegree and indegree, respectively. Leskovec et al studied the evolution of Flickr, del.icio.us, Yahoo!Answers, and LinkedIn, and examined whether the new users will preferentially link to the old users with large degrees [24]. They found that Flickr and del.icio.us show linear preference, (k) ∼ k, and Yahoo!Answers shows slightly sublinear preference, (k) ∼ k 0.9 .…”
Section: Preferential Linkingmentioning
confidence: 99%
“…Do bloggers start linking more with each other or do they tend to stay closer to their initial component? This will tell us about the cohesiveness of these clusters as they form beyond the standard "closing of the triangle" which is a general behavior of social networks (see, e.g., Wasserman and Faust 1994;Leskovec et al 2008a;Lazer et al 2010), but perhaps less so in the blogosphere when we are analyzing topics. In this case it may make more sense to talk about components or groups and monitor how far communication goes outside the initial groups as they start merging into larger communities.…”
Section: Temporal Analysis Of Communitiesmentioning
confidence: 99%